Healthy Home Education Free from Tuberculosis: Efforts to Prevent TB Transmission in the Pantai Labu Public Health Center, Deli Serdang Regency (JURNAL PENGMAS KESTRA (JPK), 2025)
Tuberculosis (TB) remains one of the major public health problems in Indonesia, including in the working area of Pantai Labu Community Health Center (Puskesmas), Deli Serdang Regency. Poor household environmental conditions—such as inadequate ventilation, insufficient lighting, and high humidity—along with unhealthy behaviors like smoking indoors, are factors that increase the risk of TB transmission. To address this issue, a Community Service Program (PKM) entitled “Healthy Homes Free from Tuberculosis Education” was implemented as an effort to improve public knowledge and behavior in preventing TB transmission through the application of healthy home principles. This activity involved 30 participants, including the general public, health cadres, and families of TB patients. The methods included interactive counseling, demonstrations of healthy ventilation, simulations of cough etiquette and clean and healthy living behaviors (PHBS), as well as direct home visits. Evaluation was conducted through pre- and post-tests and behavioral observation. The results showed an average increase in participants’ knowledge by 37.7% and positive behavioral changes, where most participants began to open ventilation daily, refrain from smoking indoors, and maintain environmental cleanliness. Additionally, five Healthy Home Cadres were formed to help sustain the program and act as advocates for health education in the community. This program proved effective in raising public awareness of the importance of healthy homes as a TB prevention measure and supports the achievement of the national End TB 2030 strategy.